DESAIN KONTROLER PIR DENGAN METODE POLE PLACEMENT PADA KONTROL MOTOR TRAKSI KERETA CEPAT - Irtania Mariska Arafanie; Mochammad Rusli; Muhammad Aziz Muslim (Jurnal Mahasiswa TEUB, 2023)
The study discusses the three-phase induction motor control response using the proportional-integralresonant control system (PIR) with the purpose of pressing the ripple on the torque output and stabilizing the output at speed. The study uses three-phase induction traction motor specifications of which one of its uses is on high-speed trains. The vector control method used is the dtc method with the svm technique. This study uses a pole placement method for determining the main parameters. Determination of the main parameter pi is determining the pole by comparing the characteristics of the polynomial with the system pole. When you get the desired pole, And it is also a Kp(speed) is 2.78 and Ki (speed) is -52.27. The value of the Kp ( torsi) is 23,661 and the Ki ( torsi) is -47,278 The value of Kp (flux) is 182,53 and Ki (flux) is - 13.3. Simulated testing uses simulink matlab software to show stability of the output speed which also reduces the ripple on the induction motor torque of three fas.3 fasa speed and motor torque with sinus wave load using pear controller generates a better response than with sinus wave load using pi controller. From the test result data that the steady state error value on the pear controller is less than 1.33 %, while the steady state error value on the greater pi controller is 22.48 %. Keywords: Three phase indution motor, PIR controller, Diret Torque Control (DTC), Pole Placement.